Determination of chlorfenvinphos in soils by microwave-assisted extraction and stripping voltammetry with an ultramicroelectrode - Morais, Simone (2013)
A methodology for the determination of the pesticide chlorfenvinphos by microwave-assisted solvent extraction and square-wave cathodic stripping voltammetry at a mercury film ultramicroelectrode in soil samples is proposed. Optimization of microwave solvent extraction performed with two soils, selected for having significantly different properties, indicated that the optimum solvent for extracting chlorfenvinphos is hexane-acetone (1:1, v/v). The voltammetric procedure is based on controlled adsorptive accumulation of the insecticide at the potential of -0.60 V (vs. Ag/AgCl) in the presence of Britton-Robinson buffer (pH 6.2). The detection limit obtained for a 10 s collection time was 3.0 x 10-8 mol l-1. The validity of the developed methodology was assessed by recovery experiments at the 0.100 µg g-1 level. The average recoveries and standard deviations for the global procedure reached byMASE-square-wave voltammetry were 90.2±2.8% and 92.1±3.4% for type I (soil rich in organic matter) and type II (sandy soil) samples, respectively. These results are in accordance to the expected values which show that the method has a good accuracy.